The Effects of Minimum Wage Throughout the Wage Distribution in Indonesia - Sri Gusvina Dewi (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2018)
The global financial crisis in 2007 followed by Indonesia’s largest labor demonstration in 2013 encouraged turmoils on Indonesia labor market. This paper examines the effect of the minimum wage on wage distribution in 2007 and 2014 and how the minimum wage increases in 2014 affected the distribution of wage differences between 2007 and 2014. This study employs recentered influence function (RIF) regression method to estimate the wage function by using unconditional quantile regression. Furthermore, to measure the effect of the minimum wage increase in 2014 on the distribution of wage differences, it uses the Oaxaca–Blinder decomposition method. Using balanced panel data from the Indonesian Family Life Survey (IFLS), it found that the minimum wage mitigates wage disparity in 2007 and 2014. The minimum wage policy in 2014 leads to an increase in the wage difference between 2007 and 2014, with the largest wage difference being in the middle distribution.DOI: 10.15408/sjie.v7i2.6125